Biomass and leaf‐level gas exchange characteristics of three African savanna C 4 grass species under optimum growth conditions - Mantlana, K. B.; Veenendaal, E. M.; Arneth, A.; Grispen, V.; Bonyongo, C. M.; Heitkonig, I. G.; Lloyd, J. (African journal of ecology, 2009)
C 4 savanna grass species, Digitaria eriantha , Eragrostis lehmanniana and Panicum repens , were grown under optimum growth conditions with the aim of characterizing their above‐ and below‐ground biomass allocation and the response of their gas exchange to changes in light intensity, CO 2 concentration and leaf‐to‐air vapour pressure deficit gradient ( D l ). Digitaria eriantha showed the largest above‐ and below‐ground biomass, high efficiency in carbon gain under light‐limiting conditions, high water use efficiency (WUE) and strong stomatal sensitivity to D l ( P = 0.002; r 2 = 0.5). Panicum repens had a high aboveground biomass and attained high light saturated photosynthetic rates ( A sat , 47 μmol m −2 s −1 ), stomatal conductance, ( g sat , 0.25 mol m −2 s −1 ) at relatively high WUE. Eragrostis lehmanniana had almost half the biomass of other species, and had similar A sat and g sat but were attained at lower WUE than the other species. This species also showed the weakest stomatal response to D l ( P = 0.19, r 2 = 0. 1). The potential ecological significance of the contrasting patterns of biomass allocation and variations in gas exchange parameters among the species are discussed. On a fait pousser des espèces herbeuses de savane de type C4, Digitaria eriantha, Eragrostis lehmanniana et Panicum repens, dans des conditions optimales dans le but de caractériser l’allocation de leur biomasse aérienne et racinaire et la réponse de leur échange gazeux à des changements d’intensité de la lumière, de concentrations de CO2, et à un gradient déficitaire (D l ) de pression de vapeur feuille‐air. D. eriantha montrait la plus grande biomasse aérienne et racinaire, une grande efficience de l’assimilation de carbone dans des conditions de luminosité limitée, une grande efficience d’utilisation de l’eau (WUE) et une forte sensibilité des stomates à D l ( P = 0,002; r 2 = 0,5). P. repens avait une grande biomasse aérienne et atteignait des taux photosynthétiques élevés en lumière saturée (A sat , 47 μmol m −2 s −1 ), et une conductance stomatique (g sat 0.25 mol m −2 s −1 ) à une WUE relativement élevée. E. lehmanniana avait une biomasse qui était presque la moitié de celle des autres espèces et avait un A sat et un g sat similaires mais qui étaient atteints à une WUE plus basse que les autres espèces. Cette espèce montrait aussi la plus faible réponse stomatique à D l ( P = 0,19, r 2 = 0,1). L’on discute de la signification écologique potentielle de ces schémas contrastés d’allocations de biomasse et des variations des paramètres des échanges gazeux entre les espèces.